Вы находитесь на странице: 1из 31

+

+

+ · · · + n + · · · =

( )

( )

n +

lim

+ ǫ >

+

+ · · · +

+

+

+ · · · +

n

< ǫ

= .
n
n ∈ N
n ≥ n
 ( ) ( )

 { a n }

+

a n = a +a + · · · +a n + · · ·

n=

 a ,a , · · · ,a n , · · ·

a n

+

n=

a n .

n N :

s n =

n

k=

a

k

{ s n }

S

{ s n }

R,

n

+s n = S

+

a n

n=

=

S.

a)

b)

c)

d)

e)

f)

g)

+

( ) n C,

n=

C R.

+

(a n+ a n , ) con { a n } una sucesion´ de numeros´

n=

+

n=

n

n

n+ .

n+

reales

+

n=

+

n=

+

n=

+

n=

 Cr n , r , C ∈ R. [a + b(n − )] , a, b ∈ R.

n .

n! .

+

n=

a n converge

+

n=n

a n converge,

 n ∈ N ∑ a n n → +∞ a n =

Si

+ a n = , entonces a n diverge

n

a)

b)

c)

d)

+

n=

+

n=

+

n=

+

n=

n .

n r ,

n

+

n

.

r < .

nπ

.

∑ a n
∑ b n
α, β ∈ R,
∑(αa n + βb
n )
∑ (αa n + βb n ) = α ∑ a n + β ∑ b n .
a
C = ,
∑ Ca n
n
a
∑ (a n +b n )
n
∑ b n
∑ a n
b n
α, β ∈ R,
∑(αa n + βb n ).

a n

a n

n N.

a n

a n

b n

a n

cb n

n n ,

 c > n ∈ N

b n

a n

a n

b n

+
a) +∞
n
,
r > .
b) +∞
c) +∞
n
r
n .
n − +sen n .
n=
n=
n=
+∞
| cscn |
d)
.
e) +∞
.
n
n
+n
n=
n=
∑ a n
∑ b n
a
n
=
∑ b n
∑ a n
b
n
→ +∞
n
a
n
= C
C
> ,
b
n
→ +∞
n
a
n
= +∞
∑ b n
∑ a n
b
n → +∞
n

a n

n

( ǫ > ) ( n N)(n m n k=m+ | a k | < ǫ )

a n

| a n |

a n

a n

 ∑ | a n |

r n

r ( , ),

+

n=

(

) n+

n

a n

|

a n | ≤ | a n |

a n

b n

b n ,

n N.

k > n N

 | a n | ≤ kb n n ≥ n , | a n | ≤ kc n , < c < k >

a n

> n , a n

n

a n , α = limsup | a n | ,

n

 ≤ α < , α > , α = , ∑ a n .

+

n=

n r .a n

r,a R.

+ a + a + a + · · · + a n + a n + · · ·

a n ,

limsup | a n+ |

| a n |

liminf | a n+ |

| a n |

a n = ,

n.

 < , > ,

limsup | a n+ | = liminf | a n+ |

| a n |

| a n |

= ,

a n .

+

n=

n r .a n

r,a R.

+ a + a + a + · · · + a n + a n + · · ·

+

n=

x n

n!

a n , a n =

+

n=

+

n+( ) n +

( ) n n

n=

n+ n

| n

n

a + ab + a b+a b +a b + · · ·

+

n=

n

n

n

n!

 { a n }

lim a n+ < lim a n lim a n < lim a n+

a

n

n
n

a

n

lim a n+

a

n

lim

n

a n

f

x k, a n ,

k N,

f (n) = a n

+

k

f (x)dx

n k,

+

n=

+

n=

+

n=

+

n=

n [lnn] p

[lnn] p

nlnn [ln(lnn)] p

(lnn) q

n

p

p

q,

 ∑ a n = A A, B ∈ R. n, s n = ∑ n k= a k ∑ b n = B t n = ∑ n k= b k , AB = n lim +∞ (s n .t n ) → = n +∞ (a +a + · · · +a n )(b +b + · · · +b n ) lim →  a b +a b + · · · +a b n    a b +a b + · · · +a b n = n lim → +∞     a b +a b + · · · +a b n    + · · · + a n b +a n b + · · · +a n b n 

n = , , , · · ·

,

d n ,

d =a b

d n =

i= a i b n +

n

n

j=

d n = a n . b n .

a n b j

+∞
+∞
k
b n ,
C k =
∑ a n b n − k , para k = , , , , · · ·
n=
a n
n=
n=
+∞
C k ,
k=
+∞
+∞
+∞
b n ,
a n b n
n=
a n
n=
n=
+∞
n+
( − )
n ,
n=

+

n=

+

n=

+

+

a n

n=

b n ,

a

n

+

n=

a n =A

n=

b n = B,

+

a n

n=

+

n=

b

n

a n

b n

AB.

A B.
A
B,

+

n=

a n ,

+

b n

n=

+

b n = B

n=

+

n=

C n

+

n=

c n

+

C n = AB.

n=

+

n=

+

a n

n=

a n = A,

+

n=

b n ,

+

n=

n(n+ )

n N,

a n =

n , b n =

(n+ ) ,

c n =

n(n+ ) d n = (n+

)

,

+

n=

a

n

+

n=

b n

+

n=

n(n+ ) +

n=

c

n

+

n=

d

n

n
{ a n }
{ b n }
A n
=
a n
k=
A −
=
.
p, q
∈ N ∪ { }
≤ p
≤ q,
q
q −
a n b n =
∑ a n (b n − b n+ ) +
A q b q − A p − b p
n=p
n=p